Accomplishment of Islamic welfare through mobilization of e-Sadaqah Jariah in the era of IR 4.0: an overview - Zainal, Noor Saliza; Mohd. Yusof, Zulkafli; Awang @ Ab. Rahman, Nurul Hidayah; Zainal, Nurul Izzah Noor; Mustafa @ Busu, Zanirah (Universiti Teknologi MARA, Kelantan, 2018)
This paper reviews the concept of welfare, sadaqah and application of e-Sadaqah Jariah in Malaysia. Basically, welfare is defined as a situation of good life for an individual or society as a whole. Practically, everyone will strive hard in order to fulfil their live with all necessities of life. But unfortunately, there are some people who unable to satisfy their needs due to economic problems, illness or disabilities. Islam as a religion of rahmatan lil alamin (blessing for all) provides various ways to tackle this situation. One of the solutions is sadaqah (charity) or sadaqa Jariah (ceaseless charity) which is a voluntary deed recommended for all Muslims. Nowadays due to the advanced technology especially in the era of Industrial Revolution 4.0, the usage of online charity or popularly known as eSadaqah is more popular compared to the traditional form. The objectives of this study have twofold. Firstly, to discuss and reemphasize the importance of sadaqah jariah. Secondly, is to clarify how to mobilize e-Sadaqah Jariah in uplifting the less fortunes in the present society of IR 4.0. The scope of study is to highlight the concept of sadaqah jariah and application of e-Sadaqah Jariah in Malaysia. This study is only a conceptualized-library research. Thus the sources information are obtained from secondary sources such as journals, books and internet. The study found that e-Sadaqah Jariah is applicable throughout the nation and on trending. Its application will facilitate the donors and speed up the collection of sadaqah to be distributed to those in need and poor.